Level 1 Evidence for Robotic Surgery for Urological and Gynecological Pelvic Cancers: Where do We Currently Stand? - Maria Chiara Sighinolfi; Giorgia Gaia; Margarita Afonina; Simone Assumma; Tommaso Calcagnile; Giulia Garelli; Mattia Sangalli; Paolo Pasquale Guarnerio; Mauro Felline; Ahmed Eissa; Luca Sarchi; Stefano Terzoni; et al. (Clinical and Experimental Obstetrics & Gynecology)
Robotic surgery is used for the surgical removal of female pelvic malignancies and encompasses procedures as radical cystectomy and radical hysterectomy. The aim of this paper is to provide an update of level 1 literature evidence about the outcomes of robotic surgery compared to other surgical approaches for the treatment of bladder, endometrial and cervical cancer. A non- systematic search of the PubMed and Scopus databases was conducted to identify peer-reviewed randomized controlled trials (RCTs) comparing surgical approaches for radical cystectomy and hysterectomy. To the purpose of capturing the lastest updates, 2020–2022 literature was reviewed. In the field of radical cystectomy, two RCTs supported the implementation of robotics as a more beneficial approach than open surgery - in terms of faster recovery, less thromboembolic events, less infectious events. In gynecology, despite robotics is accepted for the treatment of early endometrial tumors, the role of minimally invasive surgery (MIS) for the treatment of cervical cancer is still debated, with two recent systematic reviews and meta-analyses reporting conflicting results. Two- decades after the introduction of robotic surgery, there is still a number of current studies evaluating its role for the treatment of urological pelvic malignancies, especially for bladder cancer. The role of robotic surgery alone for the treatment of gynecological malignancies has been scarcely addressed with robotics being mostly evaluated as a part of MIS; updates about MIS for the treatment of cervical cancer continue to be ongoing.